STUDENTS’ NEED ON ENGLISH TEACHING MATERIALS ORIENTED TO HIGH ORDER THINKING SKILLS - Rona Rosa (Jurnal Riset Pendidikan Dasar Dan Karakter, 2021)
There are many English teaching materials that available for English teaching, but English teaching materials oriented to High Order Thinking Skills (HOTS) are the important thing that must be provided in the classroom to fulfill students’ needs in this 4.0 era. HOTS can stimulate students to apply, analyze, evaluate, and think creatively in and outside the classroom. This study is the analysis of the student’s need for English teaching materials oriented to High Order Thinking Skills in STKIP Adzkia. This research was conducted on the first-year students of STKIP Adzkia in the year 2019/2020. The sample of this study was 40 students from 147 students who were chosen randomly. The instrument in this research was a questionnaire. The questionnaire was designed to get information about the learners’ need for English materials integrated into high order thinking skills. The data were analyzed by using the descriptive method. The findings suggest that students of STKIP Adzkia need English teaching materials that are oriented to High Order Thinking Skills (HOTS). Key Words: Student’s Need; English Teaching Materials; and High Order Thinking Skills (HOTS)